Teachers Perspectives Toward english Discoveries At Universitas Muhammadiyah Surabaya - Sefiana Putri, Ruly; Hamsia, Waode (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
Integration of technology in education, particularly through platforms like English Discoveries, has transformed language learning practices at Universitas Muhammadiyah Surabaya. English Discoveries provides a multimedia-based English learning platform that supports the development of comprehensive language skills. This study aim to describe teachers' perspectives on the English Discoveries platform, identify the types of challenges teachers face in implementing the English Discoveries platform, and find out the solutions provided by teachers in overcoming challenges in implementing digital literacy on the English Discoveries platform. This mix method study explores the perspectives of 7 teachers implementing the English Discoveries platform as learning media. Through questionnaires and interviews as the instruments of this study, teachers' experiences and opinions were collected, revealing insights into their perceptions of platform usability, impact on student engagement, and improvement of English language skills. Findings of this research highlight that teachers at Universitas Muhammadiyah Surabaya have a positive perspective on the English Discoveries platform, with many supporting its use in the learning process because of the convenience it offers, such as online presence and digital checking of assignments. Nonetheless, they faced several challenges in implementing this platform, including sudden logout issues, the need for a very stable internet connection, and excessive feature complexity. To overcome these challenges, the teachers suggested the need for better support from platform managers, feature simplification, and a reliable data backup system to maintain data security and continuity, as well as ensure the platform supports various devices well. In summary, English Discoveries enhances learning, engages students, and improves teaching efficiency despite technical challenges.